Interfacial mutations in the Al‐polyimide system. (22nd March 2018) - Putz, B.; Milassin, G.; Butenko, Y.; Völker, B.; Gammer, C.; Semprimoschnig, C.; Cordill, M. J.
Abstract : Understanding the thermal stability of metal‐polymer interfaces is essential for the reliability of innovative high‐tech devices, including flexible electronics or satellite insulation. In this study, the interfacial stability of aluminum‐polyimide (Al‐PI) is investigated as a function of thermal cycling (±150°C) and thermal annealing treatments (150°C‐300°C) with X‐ray photoelectron spectroscopy measurements performed after peeling and cross‐sectional transmission electron microscopy analysis. Small mutations in the interface chemistry and structure were detected and identified after annealing at 225°C for 140 hours, including the thickness increase of an amorphous interlayer between Al and PI of about 2 nm and a change in the failure mechanism during the peeling. Being able to trace subcritical mutations before they become fatal is essential to predict the reliability and lifetime of metal‐polymer composites.